Correlation between carbon isotopic composition and morphological, micromorphological, anatomical, and physiological traits in rice - Concenço, Germani; Brito, Giovani Greigh de; Costa, Vladimir Eliodoro; Silva, Laryssa Barbosa Xavier da; Melo, Thaís Stradioto; Fagundes, Paulo Ricardo Reis; Scivittaro, Walkyria Bueno; Deuner, Sidnei (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to verify the correlations between carbon isotopic composition and traits of superior rice genotypes. Twenty genotypes were analyzed for morphology, micromorphology, anatomy, physiological performance, and carbon fingerprint. The plots consisted of 500 L plastic boxes sowed with rice, to allow of a plant density of 300 plants per square meter. Plant anatomy and physiological performance were evaluated using a microscope and an infrared gas analyzer, respectively. There is a correlation between rice water use efficiency (r = 0.45) and carboxylation efficiency (r = 0.39).